ISTRATIJIYAT ALHADITSAH FI TATHBIQ THURUQ ATTADRIS ALLUGHAH AL’ARABIYYAH (TADRIS MAHARAT ALKALAM FI JAAMIAT AL AZHAR AL INDUNISIA NAMUDZAJAN) - Faisal Hendra (El-Tsaqafah : Jurnal Jurusan PBA, 2024)
Teaching Arabic speaking skills at universities in Indonesia, many methods are used. The method is chosen based on the subject to be taught. This article aims to describe modern strategies in implementing Arabic language teaching methods. This research is considered a qualitative descriptive research type. The results of this research are as follows: (1) The process of teaching Arabic speaking skills at universities in Indonesia has been going well, however when discussing speaking skills, the data shows that college graduates do not yet have the ideal level of speaking Arabic according to the expected standards. (2) The selection and use of effective modern strategies for teaching speaking skills must be followed by various innovations in the use of teaching techniques and strategies that depend on the particular teaching methodology. (3) Using appropriate strategies that are in line with developments in science and information technology must be important for teachers or lecturers who teach Arabic language skills, especially for students from the Millennial generation and Generation Z.